Transcriptomic analysis reveals the mechanism underlying salinity-induced morphological changes in Skeletonema subsalsum - Jingwen Hu; Ya Zheng; Shuang Yang; Lin Yang; Lin Yang; Qingmin You; Quanxi Wang (Frontiers in Microbiology)
Diatom cell walls are diverse and unique, providing the basis for species identification and supporting the ecological and economic value of diatoms. However, these important structures sometimes change in response to environmental fluctuations, especially under salt adaptation. Although studies have shown that salinity induces morphological plasticity changes in diatom cell walls, most research has focused on physiological responses rather than molecular mechanisms. In this study, Skeletonema subsalsum was cultured under four salinity conditions (0, 3, 6, 12). Through morphological and physiological methods, we found that salinity increased the cell diameter, protrusion lengths, distance between adjacent cells (DBCs), and nanopore size, while reducing cell height and silicification degree. To further investigate the mechanism underlying morphological changes in S. subsalsum, complementary transcriptome analysis was performed. In total, 20,138 differentially expressed genes (DEGs) were identified among the four treatments. Among them, 231 DEGs were screened and found to be closely associated with morphological changes, of which 107 were downregulated and 124 were upregulated. The findings demonstrated that elevated salinity inhibited silicon transport and deposition via downregulating the expression of DEGs involved in functions including chitin metabolism, putrescine metabolism, and vesicle transport, resulting in reduced silicon content and cell height. Increased salinity promoted the expression of DEGs related to microtubules (MTs), actin, and ubiquitin, which synchronously induced morphological changes. These findings provide a more comprehensive understanding of the salt tolerance of algae and a foundation for future studies on cell wall morphogenesis.